On the solutions to Sylvester‐conjugate periodic matrix equations via iteration. Issue 3 (16th June 2022) - Zhang, Lei; Li, Pengxiang; Han, Mengqi; Zhang, Yanfeng; Chang, Rui; Zhang, Jinhua
Abstract: The problem of solving a class of Sylvester‐conjugate periodic matrix equations is investigated in this paper. Utilising conjugate gradient method, an iterative algorithm is provided, from which a matrix sequence can be generated to approximate the unknown matrix of the equation to be solved. Theoretical derivation proves that the proposed algorithm is convergent starting from any initial value, and simulation examples show the effectiveness of the proposed algorithm.